Vehicle Stability Control Based on Model Predictive Control Considering the Changing Trend of Tire Force Over the Prediction Horizon - Shaosong Li; Guodong Wang; Bangcheng Zhang; Zhixin Yu; Gaojian Cui (IEEE Access)
This paper proposes a vehicle stability control approach based on time-varying model predictive control to enhance the handling and stability of active front steering vehicle at the vehicle dynamics limits. The prediction equation of the proposed controller is designed based on the changing trend of tire force over the prediction horizon. Therefore, the prediction equation can represent the nonlinear characteristics in the process of prediction. To verify the effectiveness of the proposed control strategy, nonlinear model predictive controller, and previous linear time-varying model predictive controller are designed and used for comparison. Simulation experiments are performed based on the cosimulation environment of MATLAB and CarSim. At the handling limits, the control performance of the proposed controller exhibited significant improvement compared with the previous one. Moreover, its performance was close to that of the nonlinear controller, whereas its calculation speed is much faster than that of the nonlinear model predictive controller.